2017
DOI: 10.1021/acs.chemmater.7b03100
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Fe Embedded in Carbon Nanoshells–Graphene Nanomeshes with Enhanced Oxygen Reduction Reaction Performance

Abstract: Low-cost preparation of durable electrocatalysts is vital for energy storage and conversion. Here, we integrated two methods of synthesizing isolated iron atoms into a special carbon matrix as an advanced electrocatalyst. Atomic Fe isolation and graphene nanomeshes or curved carbon nanoshells were almost synthesized simultaneously. The hierarchical atomic Fe/carbon material with 0.53 atom % Fe exhibited superior oxygen reduction reaction (ORR) performance to Pt–C (20 wt % Pt) with 40 mV more positive onset pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…The N K -edge spectra of MnPc and PdMn-N 4 /CNTs are shown in Fig. 3b and there was no any significant change in the π* region, which indicated that no significant change in the coordination between Mn and N in both samples 45 .
Figure 3XAS spectra at Mn K -edge for PdMn/CNTs and PdMn-N 4 /CNTs ( a ) N K -edge for PdMn-N 4 /CNTs ( b ) core level of Pd 3d XPS spectra of Pd/CNTs, PdMn/CNTs and PdMn-N 4 /CNTs ( c ) Mn 2p XPS spectra of PdMn/CNTs and PdMn-N 4 /CNTs ( d ) and core level of N 1s XPS spectra of PdMn-N 4 /CNTs. ( e ) XAS and XPS data of pure (as purchased) MnPc is used for comparison.
…”
Section: Resultsmentioning
confidence: 92%
“…The N K -edge spectra of MnPc and PdMn-N 4 /CNTs are shown in Fig. 3b and there was no any significant change in the π* region, which indicated that no significant change in the coordination between Mn and N in both samples 45 .
Figure 3XAS spectra at Mn K -edge for PdMn/CNTs and PdMn-N 4 /CNTs ( a ) N K -edge for PdMn-N 4 /CNTs ( b ) core level of Pd 3d XPS spectra of Pd/CNTs, PdMn/CNTs and PdMn-N 4 /CNTs ( c ) Mn 2p XPS spectra of PdMn/CNTs and PdMn-N 4 /CNTs ( d ) and core level of N 1s XPS spectra of PdMn-N 4 /CNTs. ( e ) XAS and XPS data of pure (as purchased) MnPc is used for comparison.
…”
Section: Resultsmentioning
confidence: 92%
“…4c displayed four peaks, centering at 285.3, 288.3, 291.7, and 292.9 eV, respectively. The former two peaks corresponded to 1 s → π * and π * from non-graphitized atom, respectively, whereas the latter two peaks could be attributed to 1 s → σ * 32 . The unoccupied π * and σ* states indicated that the carbon was mainly in a sp 2 -like hexagonal structure, despite the presence of a disordered part 33 .…”
Section: Resultsmentioning
confidence: 95%
“…3f. This performance is among the best for the non-pyrolysis catalyst system in alkaline media, 23,[51][52][53][54] though the performance in acid media needs further improvement. Meanwhile, the much better performance of CNT@f-FeNC170 than that of the mixture of CNT and f-FeNC also verifies the importance of the intimate affinity between f-FeNC and the support/substrate.…”
Section: Ultrathin F-mnc Saec Skin Layer On Various Supportsmentioning
confidence: 99%